Ergonomic tridimensional analysis : critical ergonomic factors identification in a commercial environmental - Loureiro, Isabel F. (2012)
The Ergonomic tridimensional Analysis (ETdA) was developed to be used as an auxiliary tool on the ergonomic intervention. It was specially designed for commercial areas with free circulation of people. Due to that, the client, the third ETdA dimension, becomes an important element and their opinions relevant in the ergonomic analysis. The remains two ETdA dimensions, professionals and analyst, play an identical role as in the traditional occupational ergonomic analysis. For each of these dimensions, specific observation tools were assembled: an ETdA questionnaire, an evaluation form and a checklist for direct and indirect observations. The variables that allow the ETdA operability are identified as Ergonomic Factors (EFs). A case study is presented identifying, for each dimension, the critical EFs. This will allow the design of the weighting table, where the influence of each dimensions results is measured, stressing the important role of clients on ergonomic issues.